The Effect of Postinduction Blood Glucose on Intraoperative Hypothermia - Zhangtian Shen; Kosuke Kuroda; Hiroshi Morimatsu (Medicina, 2023)
Background and Objectives: Hypothermia frequently occurs in patients undergoing surgery and is associated with adverse complications. Therefore, this study aimed to investigate the postinduction blood glucose and occurrence of intraoperative hypothermia in patients undergoing laparoscopic surgery. Materials and Methods: This retrospective observational study included 334 patients aged ≥20 years who had undergone elective laparoscopic surgery. The primary outcome of this study was the incidence of intraoperative hypothermia. Stratified analysis revealed differences between patients with and without diabetes. Results: Hypothermia occurred in 200 (59.9%) patients. In multivariate analysis, out-of-range postinduction glucose was independently associated with hypothermia (>150 mg/dL: odds ratio 2.17, 95% confidence interval (1.02, 4.61), p = 0.045; <110 mg/dL: odds ratio 2.02, 95% confidence interval (1.15, 3.55), p = 0.015), whereas preoperative HbA1c >6% was not significantly associated with hypothermia (odds ratio 1.02, 95% confidence interval (0.56, 1.84), p = 0.961). Considering only patients with diabetes, the incidence of hypothermia was lower (p = 0.002), the duration of hypothermia was shorter (p = 0.007), and the minimum temperature was higher (p = 0.006) in those with a postinduction glucose level of 110–150 mg/dL. Conclusions: The postinduction glucose level is independently associated with intraoperative hypothermia. Out-of-range postinduction glucose appeared to have an impact on the development of hypothermia in patients with diabetes, especially those with a postinduction glucose level <110 mg/dL.